1972
DOI: 10.1073/pnas.69.12.3575
|View full text |Cite
|
Sign up to set email alerts
|

Globin Messenger RNA Activity in Erythroid Precursor Cells and the Effect of Erythropoietin

Abstract: Cell populations enriched for erythroid precursor cells were fractionated from 13-day fetal-mouse livers by a method of immune hemolysis. These preparations of precursors, contaminated by less than 7% hemoglobinized erythroblasts, synthesize globin at a rate less than 6% that of the unfractionated liver erythroid cell population. RNA was isolated from these precursor cells and assayed for globin mRNA activity in a cell-free system from Krebs ascites tumor. The 6-16S RNA fraction from precursor cells has less t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0

Year Published

1974
1974
1979
1979

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…Since in fetal liver in vivo the time for transition of a basophilic erythroblast to a polychromatic erythroblast is a few hours (15), this implies that there may be some translational control of globin synthesis at this stage of fetal liver development. Using a sensitive assay, Terada et al (3) have shown that an immature erythroid cell preparation (obtained by treatment of 13.5-day fetal liver cells with antiserum against mature red blood cells and containing not more than 7% hemoglobinized erythroblasts) synthesizes a-and B-globin chains at less than 6% of the rate for total fetal liver cells. The same workers showed that the proportion of translatable globin mRNA in the 6 16S RNA fraction from these immature cells (determined by the ability to direct a-and B-globin synthesis in the Krebs ascites cell-free system) was less than 5% of the corresponding value for total fetal liver cells.…”
Section: Relevance To Mechanism O F Control O F Globin Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Since in fetal liver in vivo the time for transition of a basophilic erythroblast to a polychromatic erythroblast is a few hours (15), this implies that there may be some translational control of globin synthesis at this stage of fetal liver development. Using a sensitive assay, Terada et al (3) have shown that an immature erythroid cell preparation (obtained by treatment of 13.5-day fetal liver cells with antiserum against mature red blood cells and containing not more than 7% hemoglobinized erythroblasts) synthesizes a-and B-globin chains at less than 6% of the rate for total fetal liver cells. The same workers showed that the proportion of translatable globin mRNA in the 6 16S RNA fraction from these immature cells (determined by the ability to direct a-and B-globin synthesis in the Krebs ascites cell-free system) was less than 5% of the corresponding value for total fetal liver cells.…”
Section: Relevance To Mechanism O F Control O F Globin Synthesismentioning
confidence: 99%
“…This work also demonstrated the presence of globin m R N A in basophiiic erythroblasts from 13-day fetal livers; whereas little globin m R N A could be detected in the more immature proerythroblasts. However, Terada et al (3) have not detected significant amounts of translatable globin m R N A in immature erythroid cells (a mixture of proerythroblasts and basophilic erythroblasts obtained by treatment of total fetal liver cells with an antiserum raised against mature red blood cells), as judged by the ability to direct globin synthesis in the Krebs ascites lysate system. These reports therefore suggest the interesting possibility that during erythroid cell differentiation globin m R N A may be synthesized before the immature erythroid cell has the capacity to translate it into globin chains.…”
mentioning
confidence: 99%
“…One of the earliest actions of erythropoietin on its target cells is the stimulation of RNA synthesis (1)(2)(3)(4)(5)(6). We have found that primary cultures of erythroid cells from human fetal liver exhibited an enhanced synthesis of heme after addition of erythropoietin or testosterone and that the heme fraction associated with hemoglobin showed the highest stimulation (7).…”
mentioning
confidence: 74%
“…This effect of erythropoietin involves an early increase in the rate of synthesis of ribosomal RNA, followed by the accumulation of mRNA for globin, stimulation of globin synthesis, and appearance of erythrocyte membrane antigens (1)(2)(3). These biochemical events are associated with morphological changes characterized by development from an early proerythroblast to a nonnucleated reticulocyte.…”
mentioning
confidence: 99%